iPSC line DHMCi019-A is generated from a patient with hereditary nephrotic syndrome harboring compound heterozygous NPHS2 variants - Tabatabaeifar, Mansoureh; Matthes, Robert; Burau, Karin; Schaefer, Franz; Jung-Klawitter, Sabine (Stem cell research, 2025)
Mutations in NPHS2, encoding the slit diaphragm protein podocin, are a common cause of steroid-resistant nephrotic syndrome in children. Over 120 mutations have been identified, leading to diverse subcellular podocin localization patterns. Peripheral blood mononuclear cells (PBMCs) were obtained from a five-year-old female patient carrying a compound-heterozygous NPHS2 mutation (c.379G>A(;)c.857_858del). Patient-derived induced pluripotent stem cells (iPSCs) were generated using the Cytotune®-iPSC 2.0 Sendai Reprogramming Kit (Invitrogen). These iPSCs exhibited normal karyotype and morphology, with confirmed expression of undifferentiated hPSC state markers and differentiation potential into all three germ layers.